A method for preparing a composite flame retardant material

By aminating the yttrium nitride micropowder and mixing it with 2,3-pyrazine diformyl chloride, a composite flame retardant material was prepared, which solved the problem of the reduction of environmental protection and material properties of existing flame retardant materials when improving the flame retardant effect of polymers, and achieved more efficient flame retardant performance and polymer performance improvement.

CN118667229BActive Publication Date: 2025-03-28SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410958397.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2025-03-28
Estimated Expiration
2044-07-17

AI Technical Summary

Technical Problem

While the existing flame retardant materials improve the flame retardant effect of polymers, they have problems such as environmental protection and pollution-free and material properties are reduced.

Method used

Yttrium nitride micropowder is used as the base material, and is mixed with 2,3-pyrazine diformyl chloride to form a composite flame retardant material, improving its flame retardant performance.

Benefits of technology

This composite flame retardant material not only shows better flame retardant effect at a smaller amount, but also improves the heat resistance, tensile strength and low-temperature brittleness of the polymer, both environmental protection and performance improvement.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for preparing a composite flame retardant material, comprising the following steps: S1, preparing amination yttrium nitride powder; S2, preparing 2,3-pyrazine dicarboxyl chloride; S3, preparing a composite flame retardant material: mixing the amination yttrium nitride powder in tetrahydrofuran, stirring evenly, adding 2,3-pyrazine dicarboxyl chloride, then adding an acid binding agent, stirring the reaction, after the reaction ends, rotary evaporation to remove the solvent, washing and drying, to obtain a composite flame retardant material. The present invention prepares a composite flame retardant material, which is not only green and environmentally friendly, but also has a better flame retardant effect under the condition that the addition amount is less than that of traditional inorganic flame retardants; in addition, it is found through the detection of the present invention that the composite flame retardant material also has a good improvement in the heat resistance, tensile strength and low-temperature brittleness of nylon materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite materials, and in particular to a method for preparing a composite flame retardant material. Background Art

[0002] Thermoplastic composite materials are currently a key industry strongly promoted by the country due to their many advantages such as light weight, good impact resistance and toughness, high fatigue strength, environmentally friendly production process, recyclability, and high production efficiency.

[0003] Flame retardant material is a protective material. It is a material that can prevent combustion but is not easy to burn itself. It is a functional additive that gives flammable polymers flame retardancy. Flame retardant materials are generally added to polymers by mechanical mixing methods to make polymers flame retardant. Flame retardant materials are mainly divided into organic flame retardants and inorganic flame retardants. Organic flame retardants are flame retardants composed of organic compounds represented by bromine, phosphorus, and nitrogen. Inorganic flame retardants are mainly flame retardants composed of inorganic compounds such as antimony trioxide, magnesium hydroxide, aluminum hydroxide, and silicon. Organic flame retardants have outstanding flame retardant effects and a wide range of applications. They have been widely used, but they are corrosive and produce smoke when burned, accompanied by the defect of toxic gas production. Inorganic flame retardant materials are currently the most commonly used type of flame retardant materials. Its main component is inorganic matter. It is not only cheap and easy to store, but the increase in the amount of flame retardant has an adverse effect on the mechanical properties and processing properties of polymer materials.

[0004] Therefore, there is a need in the market for a flame retardant material that has good flame retardant effect, is environmentally friendly and pollution-free, and does not reduce the properties of polymer materials. Summary of the invention

[0005] In view of the problems existing in the prior art, the object of the present invention is to provide a method for preparing a composite flame retardant material.

[0006] The purpose of the present invention is achieved by the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a composite flame retardant material, comprising the following steps:

[0008] S1. Preparation of amino yttrium nitride powder:

[0009] Yttrium nitride micropowder (NY) and deionized water are ultrasonically mixed, an aminosilane coupling agent is added dropwise, the temperature is raised and stirred for reaction, and after the reaction is completed, the precipitate is collected by centrifugation, washed and dried to obtain amino yttrium nitride micropowder (NH2-NY);

[0010] S2, preparation of 2,3-pyrazine dicarboxylic acid chloride:

[0011] 2,3-pyrazinedicarboxylic acid and thionyl chloride are mixed uniformly at room temperature, and refluxed and stirred for reaction. After the reaction is completed, the solvent is removed by rotary evaporation to obtain 2,3-pyrazinedicarbonyl chloride;

[0012] S3. Preparation of composite flame retardant materials:

[0013] The aminated yttrium nitride powder is mixed in tetrahydrofuran, stirred evenly, and then 2,3-pyrazine dicarboxylic acid chloride is added, and then an acid binding agent is added, and the reaction is stirred. After the reaction is completed, the solvent is removed by rotary evaporation, and a composite flame retardant material (PyAm-NY) is obtained after washing and drying.

[0014] Preferably, in S1, the particle size of the yttrium nitride powder is 150±10 μm, and the purity is higher than 99%.

[0015] Preferably, in S1, the aminosilane coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.

[0016] Preferably, in S1, the mass volume ratio of yttrium nitride powder, aminosilane coupling agent and deionized water is 1 g: (0.2-0.4) g: (20-30) mL.

[0017] Preferably, in S1, the reaction temperature is 65-75°C, the reaction time is 5-7h, and the stirring speed is 200-300r / min.

[0018] Preferably, in S1, washing is performed by washing with water at least three times, and drying is performed in a vacuum oven at 50-60°C.

[0019] Preferably, in S2, the reflux stirring temperature is 70-80°C, the reflux stirring reaction time is 3-6h, and the stirring speed is 200-300r / min.

[0020] Preferably, in S2, a small amount of DMF is added as a catalyst during the reaction, and the added amount is 1%-3% of the volume of thionyl chloride.

[0021] Preferably, in S2, the mass volume ratio of 2,3-pyrazinedicarboxylic acid and thionyl chloride is (2.52-5.04) g: (30-50) mL.

[0022] Preferably, in S3, the mass volume ratio of amino nitride yttrium powder, 2,3-pyrazine dicarboxylic acid chloride and tetrahydrofuran is 1 g: (0.68-1.36) g: (20-30) mL.

[0023] Preferably, in S3, the acid binding agent is triethylamine, and the added amount is 2%-6% of the mass of 2,3-pyrazinedicarbonyl chloride.

[0024] Preferably, in S3, the reaction temperature is room temperature and the reaction time is 8-16 hours.

[0025] In a second aspect, the present invention provides a composite flame retardant material prepared by the above-mentioned preparation method.

[0026] In a third aspect, the present invention provides an application of a composite flame retardant material in a nylon material.

[0027] Preferably, the nylon material includes any one or more mixtures of nylon 6, nylon 66, nylon 11, nylon 12, nylon 610, and nylon 612.

[0028] Preferably, the amount of the composite flame retardant material added to the nylon material is 10%-20% of the mass of the nylon material.

[0029] The beneficial effects of the present invention are:

[0030] 1. The present invention prepares a composite flame retardant material, which is not only green and environmentally friendly, but also has a better flame retardant effect when the added amount is less than that of traditional inorganic flame retardants; in addition, through the detection of the present invention, it is found that the composite flame retardant material also has a good improvement on the heat resistance, tensile strength and low-temperature brittleness of nylon materials.

[0031] 2. The composite flame retardant material of the present invention uses inorganic material yttrium nitride micropowder (NY) as a base material, and uses an aminosilane coupling agent to activate it to obtain amino yttrium nitride micropowder; then the amino yttrium nitride micropowder is mixed with 2,3-pyrazine dicarboxylic acid chloride, and an amide group is generated through the combination of acyl chloride group and amino group, so that the pyrazine group is fixed on the surface of the yttrium nitride micropowder to form a coating structure, and finally a composite flame retardant material is prepared.

[0032] 3. Compared with traditional flame retardants, the composite flame retardant material prepared by the present invention has high flame retardant performance, is compatible with the advantages of inorganic flame retardants and organic flame retardants, and also has a certain improvement on the properties of polymer materials. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0034] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0035] The reagents used in the present invention are all analytically pure; the particle size of yttrium nitride (NY) micropowder is 150±10μm, and the purity is higher than 99%; 2,3-pyrazinedicarboxylic acid (C6H4N2O4), the purity is higher than 99%.

[0036] The present invention will be further described below in conjunction with the following examples.

[0037] Example 1

[0038] A method for preparing a composite flame retardant material comprises the following steps:

[0039] S1. Add yttrium nitride powder (NY) and deionized water into a reaction bottle, place the reaction bottle in an ultrasonic machine, and perform ultrasonic treatment at 30kHz for half an hour to mix evenly, then drop γ-aminopropyltriethoxysilane (KH-550) into the reaction bottle, the mass volume ratio of yttrium nitride powder, γ-aminopropyltriethoxysilane and deionized water is 1g:0.3g:25mL, stir in a 70℃ water bath for 6h, and the stirring speed is 250r / min. After the reaction is completed, centrifuge and filter the reaction solution, wash the collected precipitate with water at least three times, and then dry it in a 55℃ vacuum oven to obtain amino yttrium nitride powder (NH2-NY);

[0040] S2, adding 2,3-pyrazinedicarboxylic acid and thionyl chloride into a reaction flask, the mass volume ratio of 2,3-pyrazinedicarboxylic acid and thionyl chloride is 3.78g:40mL, nitrogen is introduced into the reaction flask as a protective gas, and then the reaction flask is placed in a water bath pot with a reflux device, and DMF (N,N-dimethylformamide) with a volume of 2% of thionyl chloride is added dropwise as a catalyst, and after stirring evenly at room temperature, the temperature is gradually raised to 75°C, and refluxed and stirred for reaction for 5 hours at a stirring speed of 250r / min. After the reaction is completed, the solvent is removed by rotary evaporation to obtain 2,3-pyrazinedicarbonyl chloride;

[0041] S3. Mix the amination yttrium nitride powder with tetrahydrofuran, stir and mix evenly at room temperature, then add 2,3-pyrazine dicarboxylic acid chloride. The mass volume ratio of amination yttrium nitride powder, 2,3-pyrazine dicarboxylic acid chloride and tetrahydrofuran is 1g:1.02g:25mL. Then add 2%-6% of the mass of 2,3-pyrazine dicarboxylic acid chloride as an acid binding agent triethylamine. Stir at room temperature (about 25°C) for 12h. After the reaction is completed, remove the solvent by rotary evaporation, wash three times with saturated sodium bicarbonate solution, and dry to obtain a composite flame retardant material (PyAm-NY).

[0042] Example 2

[0043] S1. Add yttrium nitride powder (NY) and deionized water into a reaction bottle, place the reaction bottle in an ultrasonic machine, and perform ultrasonic treatment at 20kHz for half an hour to mix evenly, then drop γ-aminopropyltrimethoxysilane into the reaction bottle, the mass volume ratio of yttrium nitride powder, γ-aminopropyltrimethoxysilane and deionized water is 1g:0.2g:20mL, stir in a water bath at 65°C for 7h, and the stirring speed is 200r / min. After the reaction is completed, centrifuge and filter the reaction solution, wash the collected precipitate with water at least three times, and then dry it in a vacuum oven at 50°C to obtain amino yttrium nitride powder (NH2-NY);

[0044] S2, adding 2,3-pyrazinedicarboxylic acid and thionyl chloride into a reaction flask, the mass volume ratio of 2,3-pyrazinedicarboxylic acid and thionyl chloride is 2.52g:30mL, nitrogen is introduced into the reaction flask as a protective gas, and then the reaction flask is placed in a water bath pot with a reflux device, and DMF (N,N-dimethylformamide) with a volume of 1% of thionyl chloride is added dropwise as a catalyst, and after stirring evenly at room temperature, the temperature is gradually raised to 70°C, and refluxed and stirred for 6 hours at a stirring speed of 200r / min. After the reaction is completed, the solvent is removed by rotary evaporation to obtain 2,3-pyrazinedicarbonyl chloride;

[0045] S3. Mix the amination yttrium nitride powder with tetrahydrofuran, stir and mix evenly at room temperature, then add 2,3-pyrazine dicarboxylic acid chloride. The mass volume ratio of amination yttrium nitride powder, 2,3-pyrazine dicarboxylic acid chloride and tetrahydrofuran is 1g:0.68g:20mL. Then add 2%-6% of the mass of 2,3-pyrazine dicarboxylic acid chloride as an acid binding agent triethylamine. Stir at room temperature (about 25°C) for 8h. After the reaction is completed, remove the solvent by rotary evaporation, wash three times with saturated sodium bicarbonate solution, and dry to obtain a composite flame retardant material (PyAm-NY).

[0046] Example 3

[0047] S1. Add yttrium nitride powder (NY) and deionized water into a reaction bottle, place the reaction bottle in an ultrasonic machine, and perform ultrasonic treatment at 40kHz for half an hour to mix evenly, then drop γ-aminopropyltriethoxysilane (KH-550) into the reaction bottle, the mass volume ratio of yttrium nitride powder, γ-aminopropyltriethoxysilane and deionized water is 1g:0.4g:30mL, stir in a 75℃ water bath for 5h, and the stirring speed is 300r / min. After the reaction is completed, centrifuge and filter the reaction solution, wash the collected precipitate with water for at least three times, and then dry it in a 60℃ vacuum oven to obtain amino yttrium nitride powder (NH2-NY);

[0048] S2, adding 2,3-pyrazinedicarboxylic acid and thionyl chloride into a reaction flask, the mass volume ratio of 2,3-pyrazinedicarboxylic acid and thionyl chloride is 5.04g:50mL, nitrogen is introduced into the reaction flask as a protective gas, and then the reaction flask is placed in a water bath pot with a reflux device, and DMF (N,N-dimethylformamide) with a volume of 3% of thionyl chloride is added dropwise as a catalyst, and after stirring evenly at room temperature, the temperature is gradually raised to 80°C, and refluxed and stirred for reaction for 3h, and the stirring speed is 300r / min. After the reaction is completed, the solvent is removed by rotary evaporation to obtain 2,3-pyrazinedicarbonyl chloride;

[0049] S3. Mix the amination yttrium nitride powder with tetrahydrofuran, stir and mix evenly at room temperature, then add 2,3-pyrazine dicarboxylic acid chloride. The mass volume ratio of amination yttrium nitride powder, 2,3-pyrazine dicarboxylic acid chloride and tetrahydrofuran is 1g:1.36g:30mL. Then add 6% of the mass of 2,3-pyrazine dicarboxylic acid chloride as an acid binding agent triethylamine. Stir at room temperature (about 25°C) for 16 hours. After the reaction is completed, remove the solvent by rotary evaporation, wash three times with saturated sodium bicarbonate solution, and dry to obtain a composite flame retardant material (PyAm-NY).

[0050] Comparative Example 1

[0051] A flame retardant material, specifically yttrium nitride (NY) powder, with a particle size of 150±10μm and a purity higher than 99%.

[0052] Comparative Example 2

[0053] A flame retardant material, specifically 2,3-pyrazinedicarboxylic acid.

[0054] Comparative Example 3

[0055] A flame retardant material, specifically a mixture of yttrium nitride (NY) micropowder and 2,3-pyrazine dicarboxylic acid, wherein the mass ratio of yttrium nitride (NY) micropowder to 2,3-pyrazine dicarboxylic acid is 1:1.02.

[0056] Application Example 1

[0057] A flame retardant high molecular polymer is prepared by mixing American DuPont 101L nylon 66 and the composite flame retardant material (PyAm-NY) prepared in Example 1 at a mass ratio of 100:15, and extruding the mixture in a twin-screw extruder at a temperature of 220-280° C. and an extrusion speed of 500 r / min.

[0058] Application Example 2

[0059] A flame retardant high molecular polymer is prepared by mixing nylon 6 and the composite flame retardant material (PyAm-NY) prepared in Example 1 at a mass ratio of 100:10, and extruding the mixture in a twin-screw extruder at a temperature of 220-280° C. and an extrusion speed of 300 r / min.

[0060] Application Example 3

[0061] A flame retardant high molecular polymer is prepared by mixing nylon 12 and the composite flame retardant material (PyAm-NY) prepared in Example 1 at a mass ratio of 100:20, and extruding the mixture in a twin-screw extruder at a temperature of 220-280° C. and an extrusion speed of 400 r / min.

[0062] Application Example 4

[0063] A flame retardant high molecular polymer is prepared by mixing American DuPont 101L nylon 66 and a composite flame retardant material (PyAm-NY) prepared in comparative example 1 at a mass ratio of 100:15, and extruding the mixture in a twin-screw extruder at a temperature of 220-280° C. and an extrusion speed of 500 r / min.

[0064] Application Example 5

[0065] A flame retardant high molecular polymer is prepared by mixing American DuPont 101L nylon 66 and a composite flame retardant material (PyAm-NY) prepared in comparative example 2 at a mass ratio of 100:15, and extruding the mixture in a twin-screw extruder at a temperature of 220-280° C. and an extrusion speed of 500 r / min.

[0066] Application Example 6

[0067] A flame retardant high molecular polymer is prepared by mixing American DuPont 101L nylon 66 and a composite flame retardant material (PyAm-NY) prepared in comparative example 3 at a mass ratio of 100:15, and extruding the mixture in a twin-screw extruder at a temperature of 220-280° C. and an extrusion speed of 500 r / min.

[0068] Experimental testing

[0069] The flame retardant materials prepared in Example 1 and Comparative Examples 1-3 were applied to polymers (Application Example 1 and Application Examples 4-6, respectively), and various properties of the polymers after application were tested, including tensile strength, heat resistance, flame retardancy and low-temperature brittleness. The tensile strength test was based on GB / T 1040.1-2006, the heat deformation temperature test was based on GB / T 1634-2004, the limiting oxygen index test was based on GB / T 2408-2008, the vertical burning grade was based on the US UL9‎4 fire protection standard, and the low-temperature impact strength test was based on GB / T 1843-2008. The test results are shown in Table 1:

[0070] Table 1 Performance of different flame retardant materials used in polymers

[0071] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength (MPa) 113 98 85 92 Heat deformation temperature (℃) 91 79 72 75 Limiting oxygen index LOI (%) 33 30 28 29 Vertical burning UL94 grade (grade) V-0 V-1 V-1 V-1 -40℃ notched impact strength (kJ / m2) 20.4 12.1 16.7 15.8

[0072] It can be seen from Table 1 that after the flame retardant material prepared in Example 1 of the present invention is applied to polymer nylon 66, the polymer nylon 66 has higher strength, higher heat deformation temperature, better flame retardant performance, and stronger low-temperature toughness. In summary, it is shown that the flame retardant material prepared in Example 1 of the present invention can not only improve the flame retardancy of the polymer material, but also has better enhancement performance in heat resistance, tensile strength and low-temperature brittleness.

[0073] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0074] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a composite flame retardant material, characterized in that: The following steps are involved: S1. Preparation of amino yttrium nitride powder: The yttrium nitride micropowder and anhydrous ethanol are ultrasonically mixed uniformly, an aminosilane coupling agent is added dropwise, the temperature is raised and stirred for reaction, and after the reaction is completed, the precipitate is collected by centrifugation, washed and dried to obtain the amino yttrium nitride micropowder; S2, preparation of 2,3-pyrazine dicarboxylic acid chloride: 2,3-pyrazinedicarboxylic acid and thionyl chloride are mixed uniformly at room temperature, and refluxed and stirred for reaction. After the reaction is completed, the solvent is removed by rotary evaporation to obtain 2,3-pyrazinedicarbonyl chloride; S3. Preparation of composite flame retardant materials: The aminated yttrium nitride powder is mixed with tetrahydrofuran, and after being stirred evenly, 2,3-pyrazine dicarboxylic acid chloride is added, and then an acid binding agent is added, and the mixture is stirred for reaction. After the reaction is completed, the solvent is removed by rotary evaporation, and the composite flame retardant material is obtained after washing and drying. In the S3, the mass volume ratio of amino nitride yttrium powder, 2,3-pyrazine dicarboxylic acid chloride and tetrahydrofuran is 1 g: (0.68-1.36) g: (20-30) mL.

2. The method for preparing a composite flame retardant material according to claim 1, characterized in that: In S1, the aminosilane coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane; the mass volume ratio of yttrium nitride micropowder, aminosilane coupling agent and anhydrous ethanol is 1g: (0.2-0.4)g: (20-30)mL.

3. The method for preparing a composite flame retardant material according to claim 1, characterized in that: In S1, the reaction temperature is 65-75°C, the reaction time is 5-7h, and the stirring speed is 200-300r / min.

4. The method for preparing a composite flame retardant material according to claim 1, characterized in that: In S2, the reflux stirring temperature is 70-80°C, the reflux stirring reaction time is 3-6h, and the stirring speed is 200-300r / min.

5. The method for preparing a composite flame retardant material according to claim 1, characterized in that: In S2, a small amount of DMF is added as a catalyst during the reaction, and the added amount is 1%-3% of the volume of thionyl chloride.

6. The method for preparing a composite flame retardant material according to claim 1, characterized in that: In the S2, the mass volume ratio of 2,3-pyrazinedicarboxylic acid and thionyl chloride is (2.52-5.04) g: (30-50) mL.

7. The method for preparing a composite flame retardant material according to claim 1, characterized in that: In the step S3, the acid binding agent is triethylamine, and the added amount is 2%-6% of the mass of 2,3-pyrazinedicarbonyl chloride; the reaction temperature is room temperature, and the reaction time is 8-16 hours.

8. A composite flame retardant material, characterized in that: The preparation method according to claim 1 is used for preparation.

9. Use of the composite flame retardant material according to claim 8 in nylon material.

Citation Information

Patent Citations

  • Functionalized montmorillonite flame-retardant modified polypropylene composite board and preparation method thereof

    CN114685890A

  • Preparation method and application of flame retardant with heat conduction function

    CN118271998A